THREE-DIMENSIONAL NUMERICAL SIMULATION OF REACTOR AND AXIAL CYCLONE IN SEMI INDUSTRIAL SCALE - Maciel, Guilherme; Silva, Karina; Ferreira, Cassius; Luiz Borges, Valério; Carvalho, Solidônio; Braga dos Santos, Marcelo (Revista de Engenharia Térmica, 2024)
This study is motivated by the production of synthesis gas (syngas) from gasification of refused-derived fuel (RDF) in thermochemical reactors. For this purpose, a reactor with a circulating fluidized bed transforms RDF into synthesis gas at temperatures around 850°C. The syngas consists of a biphasic mixture, containing fuel gas and solid particles that are dragged during the gasification process. The gas flows into an axial cyclone positioned inside the upper part of the reactor, so that non-gasified particulates, inert residues and particles from the bed can be removed. Due to the size and density of the solid particles and the residence time inside the thermochemical reactor, the cyclone must be designed to clean the gas, improving its quality and reducing costs with scrubbers. Therefore, in this study, a vertical cylindrical reactor with 10.57 m height and 0.95 m diameter was modeled computationally, with an axial cyclone inside measuring 9.3 m in height and 0.6 m in the largest diameter region. The model does not consider thermochemical reactions inside the reactor. For the solid phase, 0.425 m³ of 100 mesh sand particles with a constant density equal to 1500 kg/m³ were considered. For the gas phase an air flow of 800 kg/h at 500°C was adopted. Numerical-computational models were solved using the ANSYS® software, based on the classical equations of mass conservation, momentum and energy. The k-omega SST turbulence model has been applied. From the analysis of pressure gradient, velocity profiles and the particulate removal rate in the cyclone, the cyclone efficiency and the pressure drop were determined. An efficiency of 99.83% in the cleaning process carried out by the axial cyclone was observed. The obtained results also allowed analyze the distribution of particles inside the reactor and their passage in the axial cyclone.